Are modal conditions necessary for knowledge? - Dacela, Mark Anthony L. (Animo Repository, 2019)
Modal epistemic conditions have played an important role in post-Gettier theories of knowledge. These conditions purportedly eliminate the pernicious kind of luck present in all Gettier-type cases and offer a rather convincing way of refuting skepticism. This motivates the view that conditions of this sort are necessary for knowledge. I argue against this. I claim that modal conditions, particularly sensitivity and safety, are not necessary for knowledge. I do this by noting that the problem cases for both conditions point to a problem that cannot be fixed even by a revised similarity ranking or ordering of worlds. I offer as groundwork a set theoretical analysis of the profiles of the problem cases for safety and sensitivity. I then demonstrate that these conditions fail whenever necessary links constitutive of the epistemic situation actually obtain but are not modally preserved. © 2019 Mark Anthony L. Dacela.